2004
DOI: 10.1902/jop.2004.75.5.744
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of InGaAsP Diode Laser Radiation to Detect Subgingival Calculus as Compared to an Explorer

Abstract: The present findings indicate that the detection of subgingival calculus is significantly improved using 655 nm diode laser radiation compared to an explorer for molars but not for single-rooted teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
2
25
0
3
Order By: Relevance
“…The challenge with the VistaCam device in its current optical configuration is that it is not designed for use in the periodontal pocket environment, but if suitable changes were made in this direction, the results from this study show promise for its eventual use for guiding clinicians in the detection of subgingival calculus. The overall approach then would be similar to using laser fluorescence to inform the decision around stopping or continuing subgingival calculus debridement (Folwaczny, Heym, Mehl, & Hickel, 2002; Krause, Braun, & Frentzen, 2003; Folwaczny, Heym, Mehl, & Hickel, 2004; Shakibaie & Walsh, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The challenge with the VistaCam device in its current optical configuration is that it is not designed for use in the periodontal pocket environment, but if suitable changes were made in this direction, the results from this study show promise for its eventual use for guiding clinicians in the detection of subgingival calculus. The overall approach then would be similar to using laser fluorescence to inform the decision around stopping or continuing subgingival calculus debridement (Folwaczny, Heym, Mehl, & Hickel, 2002; Krause, Braun, & Frentzen, 2003; Folwaczny, Heym, Mehl, & Hickel, 2004; Shakibaie & Walsh, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the accuracy of the laser-based calculus detection can be impaired by gingiva. 11,12 However, this situation was improved by the two-photon fluorescence imaging technology based on our study. While the detection of subgingival calculus by the conventional one-photon confocal microscopy technique suffered from the fluorescence of healthy cementum and the shallow penetration depth, the two-photon mechanism limited the fluorescence excitation within the focal plane and the gingiva-covered calculus.…”
Section: Resultsmentioning
confidence: 85%
“…It was suggested that the accuracy of the laser-based calculus detection can be impaired by gingiva. 11,12 The feasibility of using a multiplephoton fluorescence technique on the detection of subgingival calculus is then an interesting topic. The major impact of nonlinear optics in microscopy began with the invention of twophoton microscopy by Denk et al in 1990 (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of an automatically calculus detection system with a treatment laser is suitable, to have a minimalinvasive therapy. Previous studys with an Er:Yag-Laser with a 655nm diode detection laser showed, that the radiation induced a significant stronger fluorescence in subgingival calculus than in cementum (Folwaczny et al 2002, 2004, Krause et al, 2003.…”
Section: Introductionmentioning
confidence: 90%